Selected determinants of the frequency of consuming particular food product groups among regional-level football referees - Maria Gacek; Grażyna Kosiba; Agnieszka Wojtowicz (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
The aim of the study was to assess the frequency of consuming particular food groups among regional-level football referees depending on age, refereeing experience and sense of generalised self-efficacy. The study was conducted among a group of 138 male football referees from the Małopolska and Podkarpacie regions, using the authors' own questionnaire on food consumption frequency and the Generalised Self-Efficacy Scale (GSES). It was shown that along with the age of the referees, the frequency of consuming fruit (p < 0.001), milk and dairy products with reduced fat content (p < 0.001), poultry and cold-cuts (p < 0.01) as well as nuts (p < 0.001) increased, while the frequency of consuming white cereal products (p < 0.001) and sea fish (p < 0.05) decreased. Along with refereeing experience, the frequency of eating fruit (p < 0.001), milk and dairy products with reduced fat content (p < 0.01), poultry meat and cold-cuts (p = 0.001), nuts (p < 0.001) and alcoholic beverages (p < 0.001) increased, while the frequency of consuming white cereal products (p < 0.001), sea fish (p < 0.05) and sweet carbonated drinks (p < 0.01) decreased. A positive correlation was found between the intensity of generalised self-efficacy and the frequency of consuming milk and dairy products with reduced fat content (p < 0.01), fermented dairy products (p < 0.01), eggs (p < 0.001) and mineral water (p < 0.001) as well as dry red wine (p < 0.05), and a negative correlation was noted with the frequency of consuming pork (p < 0.05), fast food products (p = 0.001) and sweetened carbonated beverages (p < 0.001). In the examined group of regional-level football referees, there was a tendency towards more rational nutrition choices along with age and refereeing experience as well as a sense of self-efficacy, while the most explicit trends regarded relationships with the sense of self-efficacy.